The Impact of Employment Scale and Branch Network Expansion on The Sales of Loan and Deposit in Large Cooperative Banks in Poland – Implications for Operational Optimisation - Mateusz FOLWARSKI; Michał BODA; Bartlomiej BALAWEJDER (Communications of International Proceedings, 2025)
The aim of this paper was to examine the impact of branch numbers and employment levels in large Polish cooperative banks on loan and deposit sales. Using quarterly panel data from 2020–2024 for 19 banks with assets over PLN 1 billion, we applied static panel models with Driscoll-Kraay standard errors and conducted diagnostic tests to assess result stability. The findings reveal a significant non-linear effect of branch numbers and staffing on loan sales. Initial increases boost lending, but beyond a certain point, further expansion becomes inefficient, suggesting the existence of an optimal level of these resources. In contrast, no significant impact is observed on deposit values, likely due to the growing role of digital banking and remote channels. These results highlight the need for optimising branch networks and employment in large cooperative banks, particularly in the context of loan sales. Additionally, they suggest the importance of diversifying development strategies, including investments in digital banking and adapting traditional branch networks to the characteristics of the products offered.
Keywords: cooperative banks; employment; loans; deposits.